2020
DOI: 10.13057/biodiv/d210324
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric variations of Asian Common Palm Civet (Paradoxurus hermaphroditus, Pallas 1777) from Bali Island, Indonesia as the basis of morphometrics diversity data

Abstract: Abstract. Winaya A, Maftuchah, Nicolas CM, Prasetyo D. 2020. Morphometric variations of Asian Common Palm Civet (Paradoxurus Hermaphroditus, Pallas 1777) from Bali Island, Indonesia as the basis of morphometrics diversity data. Biodiversitas 21: 1027-1034. Asian Common Palm Civet (Paradoxurus hermaphroditus, Pallas 1777) is one of the small carnivores that also lives in Bali island, Indonesia. Civets can process coffee beans by fermenting them in the digestive tract, so the coffee beans have a unique aroma. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
(20 reference statements)
0
3
0
4
Order By: Relevance
“…Paradoxorus hermaphroditus is rainforest animals or civet with an important role in plant regeneration through seed dispersal (Mudappa et al 2010;Nakashima et al 2013;Winaya et al 2020). However, the International Union for Conservation of Nature (IUCN) categorizes civet on the list of least concern.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Paradoxorus hermaphroditus is rainforest animals or civet with an important role in plant regeneration through seed dispersal (Mudappa et al 2010;Nakashima et al 2013;Winaya et al 2020). However, the International Union for Conservation of Nature (IUCN) categorizes civet on the list of least concern.…”
Section: Resultsmentioning
confidence: 99%
“…However, the International Union for Conservation of Nature (IUCN) categorizes civet on the list of least concern. This means the species has the least attention because the population is considered large, therefore, they are not threatened by extinction (Duckworth et al 2016;Winaya et al 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Sebagian besar penelitian terhadap P. hermaphroditus yang telah dilaporkan oleh Maha et al (2018Maha et al ( ) dan (2019 tentang morfologi kelenjar anal dan Prastiya et al (2022) tentang morfologi dan morfometri spermatozoa, serta Winaya et al (2020) tentang morfometrik musang Bali. Penelitian mengenai morfometrik tubuh dan usus halus P. hermaphroditus di Banda Aceh dan Aceh Besar belum pernah dilakukan.…”
Section: Pendahuluanunclassified
“…Telinga dan ujung kaki juga berwarna hitam. Warna rambut coklat keabu-abuan serupa dengan P. hermaphroditus yang dilaporkan oleh Chunekar et al (2015) dan musang di Provinsi Bali dalam Winaya et al (2020). Dev et al (2015) juga melaporkan musang memiliki bintik-bintik hitam yang menyatu menjadi garis-garis di bagian sisinya; memiliki tiga garis memanjang di punggungnya; moncong, telinga, kaki bagian bawah, dan bagian distal ekornya berwarna hitam.…”
Section: Hasil Dan Pembahasanunclassified
“…Chunekar et al (2017) reported coat color variations in common palm civets from the Western Ghats. The studies by different authors demonstrated such coat colour and morphometric variations in different civets from the other parts of the globe (Eaton et al, 2010;Vasudeva et al, 2021;Veron et al, 2004;Winaya et al, 2020). Coat colour variations may be influenced by geography and climate (Ajith et al, 1998), resulting in speciation (Vasudeva et al, 2021).…”
Section: Introductionmentioning
confidence: 99%